Partisipasi Masyarakat dalam Upaya Pemulihan Wisata Pasar Mbatok Karanganyar Pasca Pandemi COVID-19 - Nurima Wibawati; Emi Widiyanti; Eksa Rusdiyana; Suwarto Suwarto (Universitas Sebelas Maret, 2024)
The Coronavirus Disease (COVID-19) pandemic that occurred in Indonesia has had a negative impact including on the tourism sector. One of the tourism areas affected by the COVID-19 pandemic is the Mbatok Market, Karanganyar, Central Java. This research aims to determine the impact of the COVID-19 pandemic on the Mbatok Market tourist community and analyze community participation in efforts to overcome the impact of the COVID-19 pandemic on Karanganyar Mbatok Market tourism. This study uses a qualitative method. The research location was carried out in Kemuning Village, Ngargoyoso Sub-district, Karanganyar Regency. Determining informants used snowball sampling and purposive sampling for key informants. Data were collected using the triangulation method based on the results of interviews with 15 informants. The results of this research show that the impact of the COVID-19 pandemic on the community at Mbatok Karanganyar Market tourism is divided into: (a) economic dimension, there is a decrease in employment opportunities, (b) social dimension, the social community that occurs as a result of the COVID-19 pandemic via online in groups WhatsApp has limitations in direct communication, (c) the cultural dimension, cultural rituals are still carried out during the pandemic but were not carried out at the start of the pandemic, (d) the environmental dimension, carried out by maintaining environmental health by implementing 3M. Community efforts to overcome the impact of the COVID-19 pandemic by implementing Community-Based Tourism which involves the entire community, traders, BUMDes, artists and youth organizations.